Effects of flavonoids on the tissue culture in radioactive technetium medium - Przybycień, Andrzej; Andryskowski, Grzegorz; Grześków, Jerzy; Bodera, Paweł (Contemporary Oncology/Współczesna Onkologia, 2002)
The study presents general information on flavonoids with particular consideration of phytoestrogens. Phytoestrogens similarly to flavonoids have differentiated pharmacological properties. Phytoestrogens decrease breast carcinoma, prostatic carcinoma and circulatory system diseases. They are thought to have radioprotective properties. In order to assess radioprotective properties of various chemical compounds, an experimental model has been created based on green monkey kidney cells culture (GMK). The culture was on radioactive technetium 99m medium. One hundred of tissue cultures were divided into 5 groups. Radioactive technetium of different activities: 10 mCi, 1 mCi, 0.1 mCi, 0.01 mCi was added in groups 1-4. Group 5 was the control group without an isotope. On the day 4 of the study lactate dehydrogenase (LDH) activity and number of cells were calculated. Radioactive technetium added into tissue culture evoked directly proportional to the used activity decrease of the number of cells and increase of their cell disintegration with subsequent LDH release. In the second part of investigations, technetium 10 mCi was added to tissue culture. The solution of formononetin, which demonstrated radioprotective properties being an antidotum to the applied agent - γ-ionising radiation, was added to part of the culture. The presented experimental model with the use of tissue culture GMK in radioactive technetium medium, what may be helpful in evaluating other flavonoid compounds of radioprotective properties. The behaviour of culture constant parameters will allow for their comparative estimation. Considerable distribution of flavonoids in nature will enable in case of natural environment contamination with radioactive compounds, to choose easily accessible material of good radioprotective properties and maybe also food as it is in case of formononetin contained in Glycine soya.